Posterior Pelvic Tilt From Supine to Standing in Patients With Symptomatic Developmental Dysplasia of the Hip. Issue 3 (9th October 2019) - Tani, Tetsuro; Takao, Masaki; Uemura, Keisuke; Otake, Yoshito; Hamada, Hidetoshi; Ando, Wataru; Sato, Yoshinobu; Sugano, Nobuhiko
ABSTRACT: Pelvic sagittal inclination (PSI) significantly affects the femoral head coverage by the acetabulum in patients with developmental dysplasia of the hip (DDH), while no reports have quantified PSI in DDH patients in the supine and standing positions. Furthermore, little is known about how PSI changes after periacetabular osteotomies. Herein, PSI in the supine and standing positions was quantified in DDH patients preoperatively and postoperatively. Twenty‐five patients with DDH who had undergone periacetabular osteotomies were analyzed. The preoperative PSI and the PSI 2 years after surgery were measured in the supine and standing positions using the image registration technique between radiographs and computed tomographic images. The percentage of patients who showed PSI changes of more than 10° from the supine to the standing position was quantified. PSI changed 8.2 ± 5.0° posteriorly from the supine to the standing position during the preoperative period. Posterior pelvic tilt of more than 10° was found in nine cases (36%). Two years after periacetabular osteotomies, the postural PSI change was 7.1 ± 3.9° posteriorly. When the preoperative and postoperative PSI values were compared, PSI in the standing position did not differ ( p  = 0.20). Similarly, the amount of PSI change from the supine to standing position was not significantly different ( p  = 0.26). In conclusion, posterior pelvic tilt in the standing position was found preoperatively in symptomatic DDH patients, and it remained for 2 years after periacetabular osteotomies. This postural change in PSI does not seem to influence the outcome of periacetabular osteotomy. However, during preoperative planning, surgeons should recognize that acetabular anteversion or anterior acetabular coverage differs between the supine and standing positions in some patients with DDH. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 38:578–587, 2020